ANALISA PENGARUH FAKTOR DEMOGRAFI DAN PROMOSI TERHADAP MUNCULNYA IMPULSE BUYING PADA PRODUK KEETORI DI SURABAYA - Kosasi, Willy Halmar (Jurnal Strategi Pemasaran, 2014)
Abstract- This study was conducted to analyze theeffect of demographic and promotion to theemergence of impulse buying on products Keetoriin PTC - Surabaya. There were 100 respondentswho contributed to this study. Criteria respondentswere aged over 17 years and have come to Keetorione time in the last 3 months. Analysis tool used isDescriptive Analysis and Regression Analysis.